Successful use of ECLS in cardiopulmonary failure due to aluminum phosphide poising - M. Mendonca; C. Tamas; L. Kiraly; H. Talo; J. Rajah (Egyptian Journal of Critical Care Medicine, 2016)
The use of ECLS in the treatment of poisoned patients has been recently reviewed by de Lange et al. [1], but a case of aluminum phosphide poising supported by ECLS has not been described yet. We want to report a successful support with ECLS in a 6 year old child with severe cardiovascular failure due to aluminum phosphide poising